Ethnolinguistics Study Of Mantra In The Tradition Of Pacu Jalur - Chairani, Sri; Nuzwaty, Nuzwaty; Barus, Efendi; Siwi, Purwanto (TELL - US JOURNAL, 2024)
The tradition of pacu jalur is one of the ancient cultures and traditions in Kuantan Singingi. Culture and language are closely related because the function of language itself is a tool for cultural development and an inventory of cultural traits. The relationship between different languages and cultures is ethnolinguistics. One of the cultures in Indonesia is mantra, which is one of the oral traditions. Mantra is considered as the oldest literary work and one of the aspects of ancient culture in Indonesia that is still maintained today. In this study, an ethnolinguistic study was conducted on the mantra of pacu jalur tradition in Kenegerian Kari Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi. The method used is qualitative-descriptive. This study shows how the sound and language of mantras in the tradition of pacu jalur, non-verbal aspects in the ritual of pacu jalur, language style, diction, denotative and connotative meaning in the mantra of pacu jalur.